Reconstruction of Islamic Da’wah Thought to Inculcate Piety and Nationalism: The Da’wah Thoughts of Habib Lutfi - bin Yahya, Luthfi; Alimi, Moh Yasir; Baedhowi, Baedhowi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
Da'wah is an effective means of the scholars to convey religious knowledge while maintaining the direction and orientation of the people. However, preaching with the provision of religious knowledge is not enough. Dai need to equip themselves with a pure heart, sincere love for others, love for the homeland, historical knowledge, respect and gratitude for previous scholars and leaders, and sincere aspirations to realize the common good, safety, prosperity and security for the wellbeing of the nation. In this article, the author, based on the thoughts and experiences of Habib Lutfi, the great Indonesian scholar who is also a reformer of Islamic da'wah in contemporary Indonesia, presents a fundamental da’wah thought reform which can be implemented in the contemporary Islamic world. Habib Lutfi's messages lay a solid foundation for da’wah based on deep spirituality, the sincerity and purity, local history, revitalization of basic religious messages such as birrul walidain, trust in God (tauhid) and tolerance; unity, love for the motherland and arousing pride in the nation's own products. Habib Lutfi also emphasized that the next generation should not disappoint their predecessors , and that unity and economic nationalism for the wellbeing of the nation is closer to daulatul Islamiyah than aspiration for the formalization of religious law. Habib Lutfi's preaching approach summarized in the love for the country has been proven to be effective in tackling the increasing hoaxes and dividing the people. Habib Lutfi's da’wah is flexible, inclusive and based on solid foundation of sanad chain.